Exploring low back pain in adolescent athletes - Wall, Julia Margaret (Trinity College Dublin. School of Medicine. Discipline of Physiotherapy, 2023)
Low back pain (LBP) is a 'pain, ache or discomfort in the low back with or without referral to the buttocks or legs.' It is known that LBP affects people of all ages. Adolescents (aged 10 to 19 years old) experience LBP regularly, although less is known about LBP in this age group. For adolescents participating in sport, LBP can disrupt the development of lifelong healthy physical activity habits in adolescence. Additionally, since a previous episode of LBP is a risk factor for future LBP, the development of LBP in adolescence can increase LBP risk later in life. The aim of this thesis was to explore and characterise LBP in adolescent athletes to inform future development of evidence-based management strategies for LBP in this population. The work in this thesis explored the epidemiology, lived experiences, and current clinician management and beliefs about LBP in adolescent athletes. Study I investigated the prevalence, incidence, risk factors, and common morphologies of LBP in adolescent athletes. It found that LBP was common in adolescent athletes, with a 12-month incidence estimate of 36.0% (95% CI 4-68, I2=99.3%), and a 12-month prevalence estimate of 42% (95% CI 29-55, I2=96.6%). Risk factors for LBP included sport participation, sport volume/intensity, concurrent lower extremity pain, overweight/high BMI, older adolescent age, female sex, and family history of LBP. Spondylolysis was the most commonly reported morphology in this population. Incidence and prevalence varied widely due to differences in methodological quality and LBP definition. Study II explored current management of LBP diagnoses in adolescent athletes. Findings showed that non-specific LBP was the largest diagnostic group in adolescent athletes, followed by spondylolysis or spondylolisthesis. There were some associations between female sex and facet-based or SI-joint pain compared to spondylolysis or spondylolisthesis. Commonly used management techniques in this cohort were diagnostic MRI, physical therapy, relative rest, and bracing. There was a high rate of imaging use although there is no consensus on imaging for spondylolysis in adolescent athletes. Study III summarised the lived experiences of adolescent athletes with LBP. The main themes were: 1) The culture of normalising LBP in sport negates safeguarding efforts aimed at protecting adolescent athletes against injury and pain, 2) LBP changes how athletes are perceived and perceive themselves, and 3) Low back pain has broad effects on the well-being of adolescent athletes. Overall, the lived experience of LBP for adolescent athletes showed that the normalisation of LBP in adolescent sport can create safeguarding risks for adolescent athletes, particularly in terms of competing with pain. Study IV examined clinician management techniques and LBP beliefs. While clinician management largely followed existing guidance on LBP management, it is important to note that there are no management guidelines or clinical pathways specific to adolescent athletes. Although LBP beliefs were largely helpful in this cohort, there were still some beliefs that were not supported by evidence held by clinicians in this participant group. Collectively, these studies aimed to explore and characterise LBP in adolescent athletes. The results of this thesis will contribute to the evidence based about LBP in adolescent athletes and may be a starting point for future research in this area to ensure optimal management of this condition. Future research in this area should focus on the development of a LBP definition and management guidelines specific to adolescent athletes, investigation into optimal methods of spondylolysis diagnosis and management, educational programmes about pain for coaches and athletes, and ongoing clinician education about LBP beliefs.
APPROVED
Keywords: low back pain; adolescent athletes; sports medicine